2023
DOI: 10.7717/peerj.16003
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional brain changes in people with knee osteoarthritis: a scoping review

Joaquín Salazar-Méndez,
Iván Cuyul-Vásquez,
Nelson Viscay-Sanhueza
et al.

Abstract: Background Knee osteoarthritis is a highly prevalent disease worldwide that leads to functional disability and chronic pain. It has been shown that not only changes are generated at the joint level in these individuals, but also neuroplastic changes are produced in different brain areas, especially in those areas related to pain perception, therefore, the objective of this research was to identify and compare the structural and functional brain changes in knee OA versus healthy subjects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…No recent ankle injury history or ankle OA existed in the recruited KOA cohort in this study, indicating a possible altered central processing on neuromuscular control in the lower limb may exist in the KOA cohort. A recent systematic review suggested that individuals with KOA showed a series of structural and functional brain changes ( Salazar-Méndez et al, 2023 ). Notably, in this clinical cohort, the reduction in grey matter was detected in the primary somatosensory cortex and the decreased connectivity bilaterally in the parietal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…No recent ankle injury history or ankle OA existed in the recruited KOA cohort in this study, indicating a possible altered central processing on neuromuscular control in the lower limb may exist in the KOA cohort. A recent systematic review suggested that individuals with KOA showed a series of structural and functional brain changes ( Salazar-Méndez et al, 2023 ). Notably, in this clinical cohort, the reduction in grey matter was detected in the primary somatosensory cortex and the decreased connectivity bilaterally in the parietal lobe.…”
Section: Discussionmentioning
confidence: 99%